2020
DOI: 10.1111/1755-6724.14596
|View full text |Cite
|
Sign up to set email alerts
|

Ore‐forming Fluid and Metallogenic Mechanism of Wolframite–Quartz Vein‐type Tungsten Deposits in South China

Abstract: South China is endowed with copious wolframite–quartz vein‐type W deposits that provide a significant contribution to the world's tungsten production. Mineralization is spatially associated with highly evolved granites, which have been interpreted as products of ancient crustal anatexis. Ore veins are mainly hosted in low‐grade metamorphosed quartz sandstone, slate and granitic rocks. The ore minerals mainly comprise wolframite, cassiterite, scheelite and pyrite, with minor molybdenite, arsenopyrite and chalco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 127 publications
0
5
0
Order By: Relevance
“…As previously mentioned, fluid mixing process did not occur in the wolframite stage at Baishitouwa, and except for minor amounts of B‐type inclusions, the ore‐forming fluids of Stages 1 and 2 contain analogical salinities (7.4–17.3 and 7.1–17.0 wt% NaCl equiv., respectively), indicating relatively constant chloride concentrations. Greisenization is often regarded as a favourable sign of wolframite mineralization in quartz–wolframite vein‐type deposits (Ni et al, 2020; Zhao et al, 2017; Zhao, Fu, et al, 2021). In the Baishitouwa deposit, greisenization predominantly occurs in a relatively narrow range on both sides of wolframite‐bearing quartz veins, which can be elucidated by the following reactions: 3NaAlSi3O8goodbreak+K+goodbreak+2H+KAl3Si3O10OH20.25em()muscovitegoodbreak+6SiO20.25em()quartzgoodbreak+3Na+ 3KAlSi3O8goodbreak+2H+KAl3Si3O10OH20.25em()muscovitegoodbreak+6SiO20.25em()quartzgoodbreak+20.12emK+ …”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, fluid mixing process did not occur in the wolframite stage at Baishitouwa, and except for minor amounts of B‐type inclusions, the ore‐forming fluids of Stages 1 and 2 contain analogical salinities (7.4–17.3 and 7.1–17.0 wt% NaCl equiv., respectively), indicating relatively constant chloride concentrations. Greisenization is often regarded as a favourable sign of wolframite mineralization in quartz–wolframite vein‐type deposits (Ni et al, 2020; Zhao et al, 2017; Zhao, Fu, et al, 2021). In the Baishitouwa deposit, greisenization predominantly occurs in a relatively narrow range on both sides of wolframite‐bearing quartz veins, which can be elucidated by the following reactions: 3NaAlSi3O8goodbreak+K+goodbreak+2H+KAl3Si3O10OH20.25em()muscovitegoodbreak+6SiO20.25em()quartzgoodbreak+3Na+ 3KAlSi3O8goodbreak+2H+KAl3Si3O10OH20.25em()muscovitegoodbreak+6SiO20.25em()quartzgoodbreak+20.12emK+ …”
Section: Discussionmentioning
confidence: 99%
“…The Linkam THMS600 stage was calibrated by measuring the melting points of pure CO 2 (−56.6 • C) and pure water (0 • C), as well as the critical point of pure water (374.1 • C). The cooling and heating stages were calibrated over a temperature range of −195 • C to 600 • C, with uncertainties of around ±0.2 • C and ±2 • C, respectively [15].…”
Section: Fluid Inclusion Microthermometrymentioning
confidence: 99%
“…High-precision geochronology and fluid source evaluation can provide key evidence for verifying their genetic link and, in turn, can guide mineral exploration and targeting. (7) Based on the data compilation of melt and fluid inclusions in W-mineralized and barren systems, it is suggested that the metallogenic potential of granite-related magmatic-hydrothermal systems is determined to a great extent by the W contents in granite melts and early-stage exsolving fluids, which, in turn, can be potential tools for W exploration.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…Wolframite-quartz vein-type tungsten deposits, generally related to granitic intrusions, are the source of much of the tungsten used by humans [1][2][3][4][5][6][7][8]. Mineralization of these deposits generally consists of wolframite (dominantly FeWO 4 or MnWO 4 ) in subhorizontal centimeter-to meter-scale quartz veins with lateral extents of hundreds of meters.…”
Section: Introductionmentioning
confidence: 99%